Perspectives on multimorbidity care provision among public hospital-based healthcare workers in Blantyre and Chiradzulu, Malawi: A qualitative study - Gift Treighcy Banda-Mtaula; Ibrahim Simiyu; Sangwani Nkhana Salimu; Stephen A. Spencer; Nateiya M. Yongolo; Marlen Chawani; Hendry Sawe; Jamie Rylance; Ben Morton; Adamson S. Muula; Eve Worall; Felix Limbani; et al. (PLoS ONE, 2026)
Multimorbidity, the presence of multiple chronic health conditions, is a leading cause of death globally. In Malawi, chronic noncommunicable and communicable diseases such as HIV frequently co-exist, putting pressure on an under-resourced system. However, the health system is primarily structured around disease-specific [vertical] programs, which hinders person-centred care approaches to multimorbidity. Our study focuses on multimorbidity care and explores the perceptions of healthcare workers on the patient pathways and service organisation throughout the patient’s interaction with the health facilities. This cross-sectional qualitative study took an interpretivist approach. We conducted 13 days of clinical observations at Queen Elizabeth Central Hospital and Chiradzulu District Hospital. We also conducted 13 days of clinical observations and semi-structured in-depth interviews with different cadres of purposively sampled healthcare workers (n = 22) at Queen Elizabeth Central Hospital and Chiradzulu District Hospital. Through thematic analysis, we identified an understanding of the organisation of care and healthcare workers’ perspectives on the delivery of services. Findings showed both hospitals provided services for inpatients and outpatients with multimorbidity, including screening, management, prevention of secondary conditions and rehabilitation. Patient diagnosis and management for multimorbidity were often delayed due to frequent stockouts of medication and consumables necessary for diagnostic testing for NCDs at the hospital level. Some healthcare workers were not equipped with the knowledge, skills, or guidelines to manage multimorbidity. As HIV care is currently better resourced than other chronic conditions, healthcare facilities may strengthen the supply chain, healthcare workers’ training sessions and monitoring and evaluation tools to ensure NCDs are well managed, learning from HIV programmes.